Chemical composition, antimicrobial, and antioxidant activity of Ulva reticulata seaweed extracted with different solvents - EMRIS FERDINAND KALE DJOH; FIRAT MEIYASA; SURYANINGSIH NDAHAWALI; NURBETY TARIGAN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Djoh EFK, Meiyasa F, Ndahawali S, Tarigan N. 2024. Chemical composition, antimicrobial, and antioxidant activity of Ulva reticulata seaweed extracted with different solvents. Biodiversitas 25: 2943-2949. Ulva reticulata Forsskal, 1775 is a green seaweed that has the potential to be developed in food, nutraceuticals, pharmaceuticals, and nutraceuticals; thus, studying the chemical composition and antimicrobial and antioxidant activities is necessary. Ulva reticulata samples were obtained from the waters of Hambuang, Haharu Sub-district, East Sumba Island, dried in the sun for three days, and floured for chemical composition analysis. In addition, water quality was tested regarding pH, Dissolved Oxygen (DO), and temperature in the Hambuang Waters. Ulva reticulata simplisia was extracted with three different solvents, namely methanol, ethyl acetate, and chloroform, and then tested for antimicrobial activity against Staphylococcus aureus Rosenbach, 1884 and Escherichia coli E and antioxidant activity. The results showed that the water quality of Hambuang was relatively good according to SNI standards with a pH value of 7.52, DO of 6.23 mg/L, and temperature of 31.30°C. Furthermore, the chemical composition of U. reticulata had a moisture content of 12.31%, ash of 23.32%, lipid of 3.04%, protein of 12.93%, and carbohydrate of 48.40%. The antioxidant activity of U. reticulata extract with methanol, ethyl acetate, and chloroform solvents were 235.31, 174.72, and 146.14 µg/mL, respectively. Furthermore, U. reticulata extract with methanol, ethyl acetate, and chloroform solvents had antimicrobial activity against S. aureus of 39.59, 33.81, 14.94 mm, and E. coli of 15.94, 17.93, 12.69 mm, respectively. Therefore, U. reticulata has the potential to be used as an ingredient in the food, nutraceutical, pharmaceutical, and cosmeceutical industries applications.